Evaluation of Erosion Rate With Small Plots and USLE Methods on Ultisol Soil Slope With Sweet Potato Plants in North Tapanuli Siborongborong - Devi Yundri Barus; Sumono Sumono; Lukman Adlin Harahap; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Agricultural cultivation, particularly food crops grown on sloping land without conservation  water and soil measures have a high erosion potential. This study was aimed to measure the erosion by determining the rate of allowable erosion  and erosion hazard level on Ultisol soil using Sweet potato intercropping with plant with slope of 9%, 21%  and 32 % that small plots and USLE methods in July-October 2012 in the Siborongborong District. The results showed the amount of erosion  using small plots for slope of  9 %, 21 % and 32 % were respectively of 0.26 tons ha-1 year-1, 0,40 tons ha-1 year-1 and 0,54 tons ha-1 year-1 respectively with low erosion hazard level category. USLE method based on 12 years of rainfall data for the slope of 9 %, 21 % and 32 %, were 42,49 tons ha-1 year-1 , 165,31 tons ha-1 year-1 and 351,35 tons ha-1 year-1 respectively with moderate to very high erosion hazard level category. USLE method based on the rainfall data 4 months  the study period for slope of 9 %, 21%, and 32 % respectively by 0,75 tons ha-1 year-1 , 2,90 tons ha-1 year-1 , and 6,09 of tons/(ha. year) with low Erosion Hazard Level category and the magnitude of the erosion rate allowed was 17.17 tons ha-1 year-1 or equal to 17,17 mm year-1. Key words: Erosion, Ultisol Soil, Sweet potato plant, Siborongborong.